2022
DOI: 10.1177/03331024221114773
|View full text |Cite
|
Sign up to set email alerts
|

The effects of certain TRP channels and voltage-gated KCNQ/Kv7 channel opener retigabine on calcitonin gene-related peptide release in the trigeminovascular system

Abstract: Background Calcitonin gene-related peptide release in trigeminovascular system is a pivotal component of neurogenic inflammation underlying migraine pathophysiology. Transient receptor potential channels and voltage-gated KCNQ/Kv7 potassium channels expressed throughout trigeminovascular system are important targets for modulation of calcitonin gene-related peptide release. We investigated the effects of certain transient receptor potential (TRP) channels the vanilloid 1 and 4 (TRPV1 and TRPV4), the ankyrin 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…A high prevalence of migraine was reported in individuals with certain mtDNA mutations 10,26 . Preclinical studies also demonstrated the activation of transient receptor potential ankyrin‐1 (TRPA1) in meningeal trigeminal nociceptors by reactive oxygen and nitrogen species (ROS/NOS), leading to neurogenic vasodilatation and CGRP release 21,27,28 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A high prevalence of migraine was reported in individuals with certain mtDNA mutations 10,26 . Preclinical studies also demonstrated the activation of transient receptor potential ankyrin‐1 (TRPA1) in meningeal trigeminal nociceptors by reactive oxygen and nitrogen species (ROS/NOS), leading to neurogenic vasodilatation and CGRP release 21,27,28 …”
Section: Discussionmentioning
confidence: 99%
“…Measurement of serum concentrations of peptides was carried out using the enzyme‐linked immunosorbent assay (ELISA) method, which has worldwide validity and reliability. Briefly, the measurements were performed as previously described by us and other groups 19–21 . HIF‐1α, FGF‐21, and GDF‐15 ELISA kits were purchased from Elabscience and CGRP, PACAP‐38, VIP, and SP ELISA kits from BT LAB.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…), the whole animal was transcardially perfused with 200 mL of phosphate‐buffered saline (pH: 7.4) through a cannula inserted into the left ventricle. Immediately after, cranial dura mater, brainstem trigeminal nucleus caudalis (TNC) and trigeminal ganglia were gently harvested as previously described by us and other groups (Citak et al, 2022; Kilinc et al, 2017; Labastida‐Ramírez et al, 2020; Rasmussen et al, 2022). Briefly, after the head was cut, the cranium was cleared of the scalp and other tissues.…”
Section: Methodsmentioning
confidence: 99%